Optimized Metallization for Interdigitated Back Contact Silicon Heterojunction Solar Cells. Issue 3 (15th March 2017) - Stang, Johann‐Christoph; Franssen, Thijs; Haschke, Jan; Mews, Mathias; Merkle, Agnes; Peibst, Robby; Rech, Bernd; Korte, Lars
Abstract : We report on the design and manufacturing of interdigitated back contact cells based on the silicon heterojunction technology. The influence of geometry and overlap of the doped amorphous silicon layers forming the contact fingers on device performance have been investigated by simulation. Two contact formation concepts, with and without a TCO interlayer – an indium tin oxide/silver (ITO/Ag) stack, and a direct aluminum (Al) metallization – are experimentally evaluated. The former retains good passivation but leads to a too high contact resistivity, the latter shows the opposite behavior, but yields a slight benefit in terms of overall performance achieving more than 20% of efficiency. We show that in this case a contact system is formed whose properties can be tuned by annealing, enabling a trade‐off between V OC and FF. Structure of the presented solar cell; a SiNX layer covers the front side, the rear side is passivated by overlapping layer stacks of intrinsic and doped amorphous silicon, the latter are contacted by aluminum. Abstract : Interdigitated back contact silicon heterojunction solar cells featuring a conventional ITO/Ag or a simple Al metallization are analyzed. The former preserves high passivation levels and thus, the open circuit voltage ( V OC ), but yields a low fill factor (FF). The latter (depicted in the figure), if annealed, enables much higher FF values at the expense of the V OC – by optimizing this trade‐off, the Al contact can outperform its ITO/Ag counterpart.